Upper gastrointestinal Kaposi's sarcoma in HIV-infected patients: ten years of endoscopy observation at a single Brazilian center. (October 2015) - Rezende, Rosamar Eulira Fontes; Kahwage, Rafael Lima; da Costa, Tarciana Vieira; Machado, Alcyone Artioli; Brunaldi, Mariângela Ottoboni; Kemp, Rafael; Módena, José Luiz Pimenta
Highlights: The study is original and describes the prevalence and clinical and pathological presentation of gastrointestinal Kaposi's sarcoma (GI KS) among HIV-infected patients undergoing upper endoscopy. GI KS is an infrequent finding among HIV-infected patients. KS lesions were found mainly in the stomach. Eighty percent of the HIV-infected patients with GI KS had concomitant skin lesions. Immunohistochemical methods (CD31, CD34, and LNA-1) are important tools in the diagnosis of lesions suggestive of GI KS. This study reports data about GI KS not yet published in our country, including the state of São Paulo. Summary: Background: Kaposi's sarcoma (KS) is the most common neoplasm among HIV-infected individuals. The frequency of involvement of KS in the gastrointestinal (GI) tract and the associated epidemiological, immune, endoscopic, and histopathological features in HIV-infected patients, were evaluated in this study. Methods: A review of the medical and endoscopy reports of 1428 HIV-infected patients, who had undergone upper GI endoscopy at the Endoscopy Service, Clinical Hospital, Faculty of Medicine of Ribeirão Preto between January 1999 and June 2009, was performed. Clinical, epidemiological, immunological, endoscopic, and histological data were collected. Results: Twenty-seven (1.9%) patients were diagnosed with GI KS. Patients were predominantly male (81.5%). Sexual activity was the main route of HIV transmission (81.5%). Cutaneous involvement was noted in 21 patients (78%). Fifteen patients (55%) received highly active antiretroviral therapy for a mean duration of 12.6 weeks (range 2–52 weeks) before endoscopy. GI lesions were mainly found in the stomach (55%). Analysis of the immunohistochemical methods HHV8 LNA-1, CD31, and CD34 for the diagnosis of gastric KS indicated high agreement (kappa = 0.63, 95% confidence interval 0.32–0.94). There was no relationship between CD4 levels ( p  = 0.34) or HIV viral load ( p  = 0.99) and HHV8 LNA-1 positivity in gastric KS. Conclusions: GI KS is an infrequent finding in patients with HIV infection. Among those with GI KS, 80% had concomitant skin lesions. Immunohistochemical methods for CD31, CD34, and LNA-1 were important tools in the diagnostic assessment of lesions suggestive of KS in the GI tract. Further studies are required to confirm these data, and the need for routine endoscopic investigation of the GI tract in HIV-infected patients with cutaneous KS should be assessed.